2012
DOI: 10.1038/cdd.2012.28
|View full text |Cite
|
Sign up to set email alerts
|

Actin reorganization as the molecular basis for the regulation of apoptosis in gastrointestinal epithelial cells

Abstract: The gastrointestinal (GI) epithelium is a rapidly renewing tissue in which apoptosis represents part of the overall homeostatic process. Regulation of apoptosis in the GI epithelium is complex with a precise relationship between cell position and apoptosis. Apoptosis occurs spontaneously and in response to radiation and cytotoxic drugs at the base of the crypts. By contrast, the villus epithelial cells are extremely resistant to apoptosis. The molecular mechanism underlying this loss of function of villus epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…These studies clearly establish a pivotal role of actin signaling linking membrane‐initiated, steroid hormone actions and regulation of cellular response mechanisms in different cancer cell types. They further support the recently postulated key role of actin remodeling in apoptosis, cell death and aging [Gourlay and Ayscough, ; Okada et al, ; Minambres et al, ; Tang et al, ; Franklin‐Tong and Gourlay, ; Smertenko and Franklin‐Tong, ; Wang et al, ]. However, although clear experimental evidence has been provided showing that early actin redistribution by steroid hormones may regulate late cellular outcomes, the apparent mechanistic link is still missing.…”
Section: Introductionsupporting
confidence: 76%
“…These studies clearly establish a pivotal role of actin signaling linking membrane‐initiated, steroid hormone actions and regulation of cellular response mechanisms in different cancer cell types. They further support the recently postulated key role of actin remodeling in apoptosis, cell death and aging [Gourlay and Ayscough, ; Okada et al, ; Minambres et al, ; Tang et al, ; Franklin‐Tong and Gourlay, ; Smertenko and Franklin‐Tong, ; Wang et al, ]. However, although clear experimental evidence has been provided showing that early actin redistribution by steroid hormones may regulate late cellular outcomes, the apparent mechanistic link is still missing.…”
Section: Introductionsupporting
confidence: 76%
“…4 Protein spots that increased in abundance over time as a result of microbial challenge increased in abundance in the challenged birds over time. As changes in actin and villin are linked to apoptotic cell death [30], the changes in the abundance of these proteins in the intestinal epithelia of the challenged birds may have contributed to the reduced growth rate and changes in protein abundance relative to the control group.…”
Section: Differentially Abundant Proteinsmentioning
confidence: 99%
“…Villin, the major actin-modifying protein associated with the microvillar actin filaments [29], remained stable over time in the control birds but decreased markedly after day 12 in the challenged birds (Table 3). Localised at the apical surface of the enterocytes, villin regulates epithelial cell morphology, actin reorganisation and cell motility; regulating cell survival by preserving steady state actin dynamics [29,30]. In the challenged birds the wide spread (over multiple spots) increase of actin, decrease in actin associated proteins, together with notable change in the abundance of villin-1, a key regulator of apoptosis in the GI epithelium [30], makes it highly likely that the microbial challenge increased apoptosis in the intestinal epithelia effecting cytoskeletal remodelling.…”
Section: Differentially Abundant Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the villin KO and villin-gelsolin double KO demonstrated greatly increased levels of epithelial cell apoptosis in response to DSS treatment [Wang et al 2012; Wang et al 2008]. Moreover, it has been previously shown that there are elevated levels of IEC apoptosis along the villus axis in the Myo1a KO [Tyska et al 2005].…”
Section: Resultsmentioning
confidence: 99%